Risks and Opportunities of Direct Democracy: The Effect of Information in Colombia’s Peace Referendum - Masullo, Juan (2019)
Voting decisions in high-stakes referendums can have crucial consequences for the fate of national governments and the implementation of major reforms. Prior studies have found that referendum campaigns can substantially influence their outcomes. Yet few have taken into account the fact that the effect of campaign arguments depends on a number of factors, including individual knowledge levels and the degree of uncertainty surrounding the alternatives on the ballot. In this study we investigate how political knowledge and campaign arguments stressing risks and opportunities influenced vote choice in Colombia’s 2016 peace referendum. Drawing on a nationally representative survey (Study 1) and an original experiment (Study 2), we find that stressing the opportunities that the peace deal could bring to the country, rather than the risks associated with failing to conclude it, increased the probability that Colombians voted Yes in the referendum. While highly knowledgeable voters were more likely to support the deal than those with little knowledge, we find that pro-referendum opportunity arguments reduced the gap between these two groups by increasing the likelihood of a Yes vote among those with little knowledge. These findings contribute to research on voting behavior and campaign effects in direct democracies. Additionally, by exploring the crucial issue of attitudes towards peace, our findings also have important implications for countries trying to secure citizens’ approval of high-stakes issues—such as negotiating the end of decades of war—through democratic instruments.